Converting Clear Cutting into a Less Hostile Habitat: The Importance of Understory for the Abundance and Movement of the Chestnut-Throated Huet-Huet (Pteroptochos Castaneus: Rhinocryptidae) - Vergara-Egert, P (Elsevier B.V., 2017)
Sustainable forest management of commercial monoculture plantations may be difficult to achieve in plantations of Monterrey pine because these commercial monocultures are managed under a clear cutting system, where the understory vegetation is initially damaged by harvesting, and subsequently, by herbicide application. Despite its marked structural changes following harvesting, the ecological role of understory in mitigating the negative impact of clear cutting on biodiversity is scarcely known. We test for the positive effect of the understory vegetation present in clearcut pine stands on the abundance and movement ability of the Chestnut-throated Huet-Huet (Pteroptochos castaneus), an insectivorous bird sensitive to adult pine plantations with scarce understory cover. Abundance was assessed through passive and broadcasting surveys during reproductive and pos-reproductive season at native forests, mature pine stands and cleacut areas. Movement was experimentally assessed as the willingness of individual Huet-Huets to enter into clearcuts from adjacent mature pint stands of native forest. The understory vegetation was the main predictor of P. castaneus abundance in native forest and mature pine plantations, but not into clearcut stands. Although Huet-Huets tended to be reluctant to enter into clearcuttings, their displacement into clearcuttings was positively influenced by the understory present in both the clearcut stands and the habitats where they had been experimentally attracted by playbacks (i.e., native forest or mature pine). We conclude that the conservation of P. castaneus in forest plantations involves modifying the traditional clearcutting system into a forest management that minimizes the use of herbicides while promoting the retention of understory vegetation and woody debris. © 2016 Elsevier B.V.